Proverbs 21:1 and Ancient Near Eastern Hydrology - Keefer, Arthur (Vetus Testamentum, 2021)
Proverbs 21:1 says that “The king’s heart is a stream of water in the hand of the Lord; he turns it to all whom he will.” The reference to “stream(s) of water” ( פלגי־מים ) is largely assumed to have a Palestinian agricultural background, and suggestions that the phrase bears any relation to foreign irrigation practices remain undeveloped. I argue, first, that these streams are artificial irrigation waterways and, second, that they connote royal ideologies which were linked to the hydrological procedures of Egypt and Mesopotamia. Most of all, their association with kingship in Prov 21:1 bears a deliberate relation to the Exodus Narrative. Based on a fresh look at written, iconographic, geographical, and archeological evidence from the wider ancient Near Eastern world, this article brings new interpretive insights to Prov 21:1 in several areas: its geographical background, its meaning, its origin, and its connection with other portions of the Hebrew Bible.